The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4012/dmj.2011-228
|View full text |Cite
|
Sign up to set email alerts
|

An approach to normalizing micro-CT depth profiles of mineral density for monitoring enamel remineralization progress

Abstract: To indicate the possibility of a new approach to creating mineral density profi les, and to examine longitudinal changes in 'the rate of remineralization (RA)' and 'the mineral density (DAs) at 4 different depths' (surface zone: SZ, lesion body: LB, middle zone: MZ, deep zone near to sound area: DZ) in enamel subsurface lesions, eight demineralized bovine enamel-dentin blocks were remineralized for 1 to 4 week and investigated using Micro-focus X-ray CT (micro-CT). After CT scanning, mineral density profi les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…It allows illustrating the inner structures with high spatial resolution in three dimensions without destruction of the specimen [18] and is sensitive enough to detect a change between demineralization and remineralization [19]. Nakata et al were able to show a strong linear correlation between the CT density and mineral content [20]. In this study, we observed an increase in mineral content in the specimen.…”
Section: Discussionsupporting
confidence: 54%
“…It allows illustrating the inner structures with high spatial resolution in three dimensions without destruction of the specimen [18] and is sensitive enough to detect a change between demineralization and remineralization [19]. Nakata et al were able to show a strong linear correlation between the CT density and mineral content [20]. In this study, we observed an increase in mineral content in the specimen.…”
Section: Discussionsupporting
confidence: 54%
“…CT is a nondestructive method that provides cross-sectional images (CT images) of objects using X-ray attenuation. A conventional micro-CT has been used in the observation of time-course changes in remineralization (Nakata et al, 2012), demineralization (Watanabe et al, 2012) and remineralization of white-spot lesions (WSL) treated with NaF plus TCP systems (Asaizumi et al, 2013). In these experiments, a CT image is expressed as a spatial distribution of so-called CT values, which correspond to the X-ray linear attenuation coefficient (X-ray LAC) of a material obtained by tomographic reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The averaged attenuation coefficients of all the tablets were then plotted against their densities to establish the relationship between the two variables 23) . The through-thickness density profiles of the exposed region obtained from the baseline, demineralization and remineralization scans were used to calculate the percentage of mineral volume recovery for each specimen using the following equation 24,25) .…”
Section: Adhesive Applicationmentioning
confidence: 99%